Surgical treatment of false aneurysm of the left ventricle after myocardial infarction. - Shabbo, F P (1983)
Rupture of the left ventricle after myocardial infarction results either in sudden death from cardiac tamponade or, when pericardial adhesions are present, in bleeding that is confined to a limited space, which gradually expands as the blood flows through a small communicating orifice under high pressure, forming a false aneurysm. In three such patients a false aneurysm of the left ventricle after myocardial infarction was successfully treated by operation. The interval from the initiating event to the time of surgery averaged 10 months. Two of the patients had pericarditis and all presented at some stage of the illness with tachyarrhythmias and cardiac failure. All the patients survived operation and have improved functionally. Because of the propensity of false aneurysms to rupture, early diagnosis and aggressive surgical treatment are recommended.